Silica Immobilized Second Generation Hoveyda-Grubbs: A Convenient, Recyclable and Storageable Heterogeneous Solid Catalyst - Van Berlo, Boris; Houthoofd, Kristof; Sels, Bert F.; Jacobs, Pierre A. (Advanced synthesis & catalysis, 2008)
The second generation Hoveyda–Grubbs metathesis catalyst was successfully immobilized on silica in pellet and powder form following a practical and fast synthesis procedure. The activity of the solid system is truly heterogeneous, efficient in various metathesis reaction types and stable for at least 4000 TON. Ru contamination of the products was very low (ppb levels). The successful use of the robust system has been demonstrated in a continuous reactor set‐up.